Correlating HIV tropism with immunological response under combination antiretroviral therapy. Issue 8 (17th March 2016) - Bader, J; Schöni‐Affolter, F; Böni, J; Gorgievski‐Hrisoho, M; Martinetti, G; Battegay, M; Klimkait, T; ,
Abstract : Objectives: A significant percentage of patients infected with HIV‐1 experience only suboptimal CD4 cell recovery while treated with combination therapy (cART). It is still unclear whether viral properties such as cell tropism play a major role in this incomplete immune response. This study therefore intended to follow the tropism evolution of the HIV‐1 envelope during periods of suppressive cART. Methods: Viruses from two distinct patient groups, one with good and another one with poor CD4 recovery after 5 years of suppressive cART, were genotypically analysed for viral tropism at baseline and at the end of the study period. Results: Patients with CCR5‐tropic CC‐motif chemokine receptor 5 viruses at baseline tended to maintain this tropism to the study end. Patients who had a CXCR4‐tropic CXC‐motif chemokine receptor 4 virus at baseline were overrepresented in the poor CD4 recovery group. Overall, however, the majority of patients presented with CCR5‐tropic viruses at follow‐up. Conclusions: Our data lend support to the hypothesis that tropism determination can be used as a parameter for disease progression even if analysed long before the establishment of a poorer immune response. Moreover, the lasting predominating CCR5‐tropism during periods of full viral control suggests the involvement of cellular mechanisms that preferentially reduce CXCR4‐tropic viruses during cART.